Analisis Tingkat Pemahaman Mahasiswa Program Studi Pendidikan Agama Islam Pada Mata Kuliah Psikologi Perkembangan (Tarbiyah Suska Conference Series, 2023)
The purpose of this study was to describe the level of understanding of islamic religious education students after attending a student developmental psychology course. After following these courses, students as prospective teachers so that during the learning process is achieved, then one knows how to implement learning methods and use, educational and learning materials, know the psychological signs of students at each certain level of development in the form of attitudes and behavior, understand the character of students in developing various types of abilities and potentials, and complete learning programs based on knowledge of developmental psychology. The method in this research is descriptive descriptive which describes the behavior of the subject whose type is studied. Then the position of researchers in this study as the main research instrument. Open questionnaires and observations are sources of data in this study as primary data obtained by respondents. While the documentation of programs in the developmental psychology course of students as secondary data in the form of. Methods of observation, questionnaires, and documentation used as data collection in this study. Furthermore, this study uses qualitative data analysis and data triangulation techniques as a test of the validity of the data in this study. The results of this study suggest that students of the islamic religious education study program at muhammadiyah university of jakarta have a level of understanding about development and problems, study behavior and traits, train motor skills, educate and shape character according to religious values, understand feelings, motivate, developmental factors , knowing good problem solving, the right strategy used by an educator, and being able to find treatment, and can guide children's development to the best stage of development for students.
Keywords: Level of Understanding; Student; PAI, Developmental psychology